2022
DOI: 10.2147/rru.s332578
|View full text |Cite
|
Sign up to set email alerts
|

MicroRNAs as Potential Liquid Biopsy Biomarker for Patients with Castration-Resistant Prostate Cancer

Abstract: Purpose To identify micro-RNAs (miRNAs) expression profiles in peripheral blood plasma that could play a role as potential biomarkers in patients who progressed to castration-resistant prostate cancer (CRPC). Liquid biopsy analysis of miRNAs is a fast-developing field with a considerable likelihood to predict tumor progression and metastasis by targeting genes involved in oncogenesis. Patients and Methods Differential expression analysis of miRNAs profile in CRPC patien… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 36 publications
(45 reference statements)
0
3
0
Order By: Relevance
“…Notably, a recent study by Fernandez et al. found that miR-6514-3p is upregulated in prostate cancer patients, indicating its potential role as a prognostic marker in prostate cancer ( 48 ). Among the miRNAs described in our study, miR-134-3p is of particular interest because it enhanced the expression of all three ICMs investigated, that is, ENTPD1, NT5E, and CD274.…”
Section: Discussionmentioning
confidence: 99%
“…Notably, a recent study by Fernandez et al. found that miR-6514-3p is upregulated in prostate cancer patients, indicating its potential role as a prognostic marker in prostate cancer ( 48 ). Among the miRNAs described in our study, miR-134-3p is of particular interest because it enhanced the expression of all three ICMs investigated, that is, ENTPD1, NT5E, and CD274.…”
Section: Discussionmentioning
confidence: 99%
“…Among the peculiarities of this system is its intrinsic ability to detect neoplastic disorders even in patients who had only dysplastic lesions or cancers in situ, and its ability to detect cancer factors even years after the resection of the primary tumor to predict metastatic recurrence. In this regard, MATERD sensitivity is higher than the latest liquid biopsy tests based on the detection of circulating cancer cells, circulating DNA and circulating miRNA [ 184 , 185 , 186 ]. The clinical results obtained with the MATERD test confirm that (i) cancer factors circulate in the blood prior to the complete cancerous transformation of the cells, undermining the concept that cell circulation is paramount to metastasis formation in distant organs [ 181 , 182 , 183 ], and (ii) cancer factors are still found circulating in the serum after primary cancer has been removed and for several years afterwards, therefore strengthening the concept that these factors do not require the presence of cancer cells to induce metastatic disease [ 181 , 182 , 183 ].…”
Section: Horizontal Transfer Of Malignant Traits Modelmentioning
confidence: 99%
“…For RNAs to be robustly analyzed in liquid biopsies, they need to survive the RNase-rich extracellular environment. Certain RNA species, such as the microRNAs (miRNA), exhibit greater stability, can be abundant with high specificity in patient plasma and are increasingly explored ( 22 , 23 ). The formation of RNA-protein, RNA-DNA and RNA-lipid complexes are potential mechanisms mediating this increased stability of endogenous RNA transcripts.…”
Section: Liquid Biopsy Analytes Commonly Used In the Clinical Practicementioning
confidence: 99%